(In)consistências da gestão social e seus processos de formação: um campo em construção - Araújo, Edgilson Tavares de (2012)
The social management increasingly established itself as the object of proposals for training in higher education at undergraduate and graduate levels, mobilizing an increasing number of institutions and agencies, as well as teachers, students and professionals related to teaching, research and extension. This thesis aims to understand the general elements that provide consistency / inconsistency in the concept of social management by examining the processes of the training of social managers. Through the perceptions of actors and writers who are part of the field, the scope of the construct, the dynamics of education and their training content are analyzed. It is argued that there are (in)consistencies in plural conceptions of social management that are manifested in the education processes, influencing speeches and practices of social managers, highly dedicated to advancing the public and rights of citizenship, but also prevailing logic and ideologies ambiguous and ambivalent, focused on the private management and instrumentality. It is also said that what is taught is not known very well, what is the social management, whose nature and limits are still in the process of consolidation (in progress) with early institutionalization, setting up an interdisciplinary field of construction. Through historical review of concepts and facts generated from the field, from social management courses and subjects, it was possible to identify social epistemological and methodological issues and identify what stage of institutionalization the social management is. The methodology is qualitative, with content analysis of 31 (thirty one) semi-structured interviews with teachers and students of training programs (undergraduate and strict sensu graduate studies) of six higher education institutions in Brazil and documents analysis (educational projects, course plans, promotional materials). The results indicate that the social management: is not a discipline or a paradigm itself, but an expanding interdisciplinary field that arises from universities of the country and is attracting different actors for opportunities for migration issue and recognition by needs and by vocation and identity. The education processes have several innovations in curriculum measures. Logical and unambiguous plural concepts of social management stand out, defined by non precise concepts, goal of the management, management way/process, field and/or concept under construction. Live with ambiguities and ambivalences as: the logic of public and/or private, the instrumental and ideological, professional and critical nature; consistent or weak and inaccurate concepts, concentration of capital and/or social management; exogeny or endogenous knowledge; disciplinary or multidisciplinary production, regulated/institutional production or useful/creative production, knowledge about social management or knowledge in social management